2000
DOI: 10.1159/000014265
|View full text |Cite
|
Sign up to set email alerts
|

Catch-Up Growth in 166 Small-for- Gestational Age Premature Infants Weighing Less than 1,000 g at Birth

Abstract: Catch-up growth was studied in 166 children born with an extremely low birth weight (<1,000 g) and small-for-gestational age (SGA, <10th percentile birth weight for gestational age). Of these children 159 were followed up for between 4 and 18 years (median 9 years). Group A, SGA <10th percentile of Lubchenco curves only; group B, <10th percentile of Mamelle’s curves but >5th percentile, and group C, <5th percentile of Mammelle’s curves. Catch-up growth was considered to be achieved when height, weight, and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 37 publications
5
29
1
5
Order By: Relevance
“…Investigators have reported retarded height and weight growth among LBW, especially in VLBW children [10] [11]. Although most LBW children experience catch-up growth by adolescence, the precise time of catch-up is highly diverse and appears to depend on their weight and gestational age at birth [6]- [9]. In fact, several studies have reported that SGA infants were more likely to remain smaller throughout childhood and adulthood than infants born at weights appropriate for gestational age (AGA) [8] [11] [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators have reported retarded height and weight growth among LBW, especially in VLBW children [10] [11]. Although most LBW children experience catch-up growth by adolescence, the precise time of catch-up is highly diverse and appears to depend on their weight and gestational age at birth [6]- [9]. In fact, several studies have reported that SGA infants were more likely to remain smaller throughout childhood and adulthood than infants born at weights appropriate for gestational age (AGA) [8] [11] [28].…”
Section: Discussionmentioning
confidence: 99%
“…After initial postnatal growth failure, most preterm infants exhibit catch-up growth in weight, height, and head circumference, generally starting early in the neonatal period and with catch-up occurring by early infancy [6] [7]. However, some investigators have reported delayed catch-up growth to childhood [7] [8] or adolescence [9].…”
Section: Introductionmentioning
confidence: 99%
“…40 One aspect peculiar to this study was the presence of 37 sets of twins/triplets. In a subsequent study, 36 pairs of premature infants less than 1,000 g in which one sibling was small for gestational age and another was appropriate for gestational age were studied with the aim of investigating the role of IUGR and the postnatal environment on the growth, development and academic performance of these children.…”
Section: Important Conceptsmentioning
confidence: 97%
“…11,[36][37][38][39][40] Intrauterine growth restriction is a common pathological condition, especially in developing countries, and has awakened great concern because of its association with future diseases of adulthood, such as : arterial hypertension, diabetes, hyperlipidemia and coronary disease. 41 Although a majority (80%) of babies born with IUGR exhibit catch-up growth during the first 2 years of life, generally during the first 6 months, there is great concern for those that do not catch up, since these children have a worse prognosis for intellectual development 42 and half of them will also become adults of small stature.…”
Section: Important Conceptsmentioning
confidence: 99%
See 1 more Smart Citation